الأفعال المزيدة في مسرحية التحطيم للكاتب الليبي علي الفلاح - دراسة صرفية معجمية دلالية - خبيزة سمية رمضان (مجلة الاصالة, 2024)
الأفعال المزيدة في مسرحية التحطيم للكاتب الليبي علي الفلاح - دراسة صرفية معجمية دلالية